Density and Acidic Solution Calorimetry Studies of the 0.333CaO-0.667[xSiO2-(1-x)P2O5] Glassy System (JOURNAL OF ADVANCES IN CHEMISTRY, 2009)
Glassy samples of the 0.333CaO-0.667[xSiO2-(1-x)P2O5] system are prepared by the melt quenching technique. Accurate density and solution enthalpy measurements were performed by pycnometry at 296.15 K and acid solution calorimetry at 298.15 K, respectively. Excess molar volume and mixing enthalpy from the ideal behavior over the entire mole fraction range were calculated. These excess thermodynamic properties are negative over the whole composition range showing attractive and contraction behavior with the increase in the silica content. Excess properties were fitted to the Redlich-Kister type equation. Examination of the behavior of the excess properties indicates that deviations from ideality can be attributed mainly to the formation of mixed association complexes.